THE IMPACT OF THE 2008 GLOBAL CRISIS ON THE DEPTH OF THE FINANCIAL SYSTEM - HALIL D. KAYA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
This study examines how the depth of the financial system around the world have changed before, during, and after the 2008 Global Crisis. In total, we examine nine variables related to the depth of the financial system. Two of these variables are related to the depth of the stock market, four of them are related to outstanding amounts of public and private debt, one variable is related to the amount of international debt offerings, and four variables are related to the amount of equity and debt instruments in portfolios. When we examine the year preceding the crisis, we find that two of the variables had changed significantly. These are the “stock market capitalization” and the “stock market total value traded” variables. Both of these variables had gone up significantly before the crisis. We do not see any significant change in the other nine variables. When we examine the crisis period, we find that the “stock market capitalization” started to go down and also the “gross portfolio equity liabilities” went down significantly. None of the other variables had changed during the crisis period. Finally, when we examine the year following the crisis, we find that “stock market capitalization” went down significantly. None of the other variables had changed significantly during the year following the crisis. Policymakers can use these findings to evaluate the chances of a new crisis happening and also to take precautions beforehand.